TERDAFTAR SEBAGAI PENDUDUK DAN BERTEMPAT TINGGAL BAGI CALON KEPALA DESA - Setiadi, Tedy; Rusdianto; Pramudya, Rorry; Hartono; Setiawan, M. Budhi (The Juris, 2024)
The Constitutional Court, in Decision No. 65/PUU-XXI/2023, has regulated the conduct of campaigns in educational institutions. This research aims to analyze the Ratio Decidendi of the Constitutional Court Decision No. 65/PUU-XXI/2023. The research method used is normative research with a qualitative approach, utilizing legislative and case approaches. In its decision, the Constitutional Court deemed that the absolute prohibition of educational institutions as campaign venues contradicts Article 28E paragraph (3) of the 1945 Undang-Undang Dasar of the Republic of Indonesia concerning the freedom of association, assembly, and expression of opinion. The analysis results indicate that this decision represents a significant breakthrough in upholding the constitutional rights of citizens to express opinions publicly. However, the absence of more detailed and operational norms in this Constitutional Court decision may lead to various interpretations and different understandings among the public, as the decision does not provide clear boundaries and criteria on the forms of campaign activities allowed or prohibited in educational environments. To effectively implement this decision, it is hoped that the General Elections Commission (KPU) and the Election Supervisory Body (Bawaslu) will formulate strong oversight and law enforcement mechanisms, as well as swift corrective actions for violations to ensure fair and orderly campaign practices.